Characterizing visual field loss from past mercury exposure in an Indigenous riverine community (Grassy Narrows First Nation, Canada): a cluster-based approach - Aline Philibert; Benoit Tousignant; Myriam Fillion; Judy Da Silva; Donna Mergler (BMC, 2024)
Abstract Background Between 1962 and 1975, a chlor-alkali plant in Canada discharged approximately 9 metric tons of mercury (Hg) into the Wabigoon River. Over the following decades, biomarkers of Hg exposure of persons from Grassy Narrows First Nation (Asubpeeschoseewagong Anishinabek), located downriver from the discharge, reflected Hg concentrations in fish. Hg exposure is known to target the calcarine fissure, resulting in visual field (VF) loss. Most studies and clinical reports focus solely on peripheral VF loss; little is known about the impact of Hg on the central and paracentral portions. The present study sought to characterize the patterns of VF loss with respect to past and current Hg. Methods A 28-year hair-Hg (HHg) database, created from a 1970-97 government biomonitoring program, served to select study participants with ≥ 4 year-based HHg measurements (n = 81). Blood-Hg was assessed for current exposure. Light sensitivity thresholds across the VF were analyzed monocularly, using a Humphrey Field Analyzer (HFA). Following post-hoc exclusions, based on HFA interpretation indices, 65 participants were retained. Both eyes were combined for analyses (n = 130 eyes). Unsupervised hierarchical clustering of HFA plot data was used to identify patterns of VF loss. A series of mixed effects models (MEM) were performed to test the associations for current Hg exposure with respect to HFA interpretation indices and clusters, as well as for longitudinal past Hg exposure. Results The clustering approach decomposed the light sensitivity deficits into 5 concentric clusters, with greatest loss in the peripheral clusters. No relation was observed between any of the cluster scores and current blood-Hg. VF deficits increased with past Hg exposure. Longitudinal MEM showed that HHg was significantly (p < 0.05) associated with all peripheral, paracentral, and central cluster scores, as well as with HFA interpretation indices. Conclusions Past Hg exposure in Grassy Narrows First Nation was associated with present day VF loss. The cluster-based location-specific approach identified patterns of VF loss associated with long-term Hg exposure, in both the peripheral and the central areas. The functional implications of this type of visual loss should be investigated.